Effect of exercise duration on plasma endothelin-1 concentration - Davis, P. G.; Ferguson, M. A.; Alderson, N. L.; Pate, R. R.; Bodary, P. F.; Durstine, J. L. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: Endothelin-1 (ET-1) is a potent vasoconstricting peptide released mostly from vascular endothelial cells. Isolated exercise sessions of relatively long duration (>=30 min) have produced increases in plasma ET-1 concentration while shorter exercise sessions usually have not. The purpose of the present study was to verify an effect of exercise duration at a steady work rate on plasma ET-1 concentration. Methods: Eleven endurance-trained males (age 27±6 years; maximal oxygen consumption‹V.O2max‹56±7 mL·kg-1·min-1, body fat 11±5%; mean±SD) exercised on a treadmill at 70% V.O2max on 2 occasions separated by at least 2 weeks. During a short-duration session, subjects expended approximately 3 360 kJ (60±2 min). During a long-duration session, subjects expended approximately 6 300 kJ (112±4 min). Six of the subjects performed the 3 360 kJ session before the 6 300 kJ session while the other 5 subjects performed the 6 300 kJ session first. Results: The short-duration session did not cause plasma ET-1 concentration to change immediately after exercise (0.23±0.01 pmol·L-1 before exercise, 0.22±0.02 pmol·L-1 after exercise, mean±SE). However, 10 of 11 subjects had increased ET-1 after the long-duration session (0.28±0.02 pmol.L-1 before exercise, 0.32±0.02 pmol·L-1 after exercise, P=0.0004). A treatment-by-time effect was present (P=0.003). Conclusion: These results demonstrate an effect of exercise duration on plasma ET-1 concentration. Exercise duration is, therefore, an essential consideration when investigating exercise's effect on ET-1.